A new strategy for plyometric training on national-level jumpers and sprinters. A cross-sectional randomized crossover study - Montoro, R.; Sousa, P.; Costa, A.; Pinheiro, V.; Sarmento, H.; Rama, L. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: The integral reactive strength index (IRSI) has recently been described in the literature as a marker that could allow better control of plyometric training programs. This study aimed to compare the effects of a plyometric training program based on the IRSI versus a traditional jump training program on spatiotemporal variables associated with the performance of national-level jumpers and sprinters. METHODS: A cross-sectional, randomized, repeated measures crossover study was conducted. Twenty-seven male track and field athletes were divided in three groups. Group 1 (G-RT1 = 9) began the experiment with IRSI-based plyometric training, group 2 (G-PT2 = 10) began the experiment with traditional plyometric training, and (a control) group 3 (G-CT3 = 8) continued its usual training without any specific plyometric intervention. RESULTS: After 19 weeks of the experiment, a two-way mixed analysis of variance for the G-RT1 group found a significant interaction and large effect sizes (ES) in the group-time relationship in the 60m dash (p * 0. 001; f = 101.2; *2 = 0.089), and the standing triple jump (STJ) (p * 0.001; f = 119.8; *2 = 0.031). The G-PT2 also showed better results, but the ES was lower for the standing long jump (p * 0.001; f = 52.7; *2 = 0.045), and the STJ (p * 0.001; f = 22.7; *p2 = 0.011). Meanwhile, the G-CT3 did not show significant improvement at the end of the program. CONCLUSION: It has been demonstrated that the use of ISRI-based plyometric training programs produces better results than traditional ones. The use of ISRI-based practice improves individualization, emphasizes high-intensity maintenance, and induces better results with less cumulative work.